Photodynamic antimicrobial therapy of curcumin in biofilms and carious dentine - Araújo, N. C.; Fontana, Carla Raquel [UNESP]; Bagnato, V. S.; Gerbi, M. E M (Springer Nature, 2013)
Photodynamic therapy (PDT) is a technique that involves the activation of photosensitizers by light in the presence of oxygen, resulting in the production of reactive radicals that are capable of inducing cell death. The present study evaluated the susceptibility of Streptococcus mutans and Lactobacillus acidophilus to PDT grown as multi-species in the biofilm phase versus in dentine carious lesions. A brain-heart infusion culture medium supplemented with 1 % glucose, 2 % sucrose, and 1 % young primary culture of L. acidophilus 108 CFU/mL and S. mutans 108 CFU/mL was used to develop multi-species biofilms and to induce caries on human dentine slabs. Five different concentrations of curcumin (0.75, 1.5, 3.0, 4.0, and 5.0 g/L) were used associated with 5.7 J/cm2 light emission diode. Four different groups were analyzed L-D- (control group), L-D+ (drug group), L+D- (light group), and L+D+ (PDT group). ANOVA/Tukey's tests were conducted to compare groups. A significant reduction (p <0.05) in cell viability was observed in the biofilm phase following photosensitization with all curcumin concentrations tested. To achieve significant bacterial reduction (p <0.05) in carious dentine, it was necessary to utilize 5.0 g/L of curcumin in association with blue light. No significant reduction was found for L-D+, supporting the absence of the drug's dark toxicity. S. mutans and L. acidophilus were susceptible to curcumin in the presence of blue light. However, due to light penetration and drug diffusion difficulties, these microorganisms within dentine carious lesions were less affected than they were in the biofilm phase. © 2013 Springer-Verlag London.
Keywords: Biofilms; Cariogenic bacteria; Curcumin; Dentine; Photodynamic therapy; Streptococcus mutans